1977
DOI: 10.1107/s056773947700031x
|View full text |Cite
|
Sign up to set email alerts
|

The structure of NaTaO3by X-ray powder diffraction

Abstract: The structure of NaTaO3 has been determined from X-ray powder diffraction spectra by measuring the intensities of the difference reflexions caused by the deviations from the ideal cubic perovskite structure. The structure is compared with that determined on the basis of single-crystal measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 9 publications
(14 reference statements)
3
30
0
Order By: Relevance
“…1,2 This structure rules out the possibility of ferroelectricity for this compound, claimed previously by some authors, 3,4 and showed by similar materials like NaNbO 3 5,6 and BiInO 3 . 7 The centrosymmetrical nature of NaTaO 3 was also confirmed by the absence of characteristic dielectric anomalies in a very large temperature interval and of polarization loops in ceramics and single crystals.…”
Section: Introductionmentioning
confidence: 58%
“…1,2 This structure rules out the possibility of ferroelectricity for this compound, claimed previously by some authors, 3,4 and showed by similar materials like NaNbO 3 5,6 and BiInO 3 . 7 The centrosymmetrical nature of NaTaO 3 was also confirmed by the absence of characteristic dielectric anomalies in a very large temperature interval and of polarization loops in ceramics and single crystals.…”
Section: Introductionmentioning
confidence: 58%
“…All of the ATaO 3 (A = Na and K) consist of corner-sharing TaO 6 octahedra with perovskite-like structure. The bond angles of Ta-O-Ta are 163 • (NaTaO 3 ) [14] and 180 • (KTaO 3 ) [15]. It has been reported by Wiegel et al [16] that in alkali tantalates, as the bond angle is close to 180 • , the band gap becomes smaller and the delocalization of the excited energy is larger.…”
Section: Resultsmentioning
confidence: 97%
“…The Na cation is surrounded by 12 O anions in a dodecahedral environment, the Ta cation is octahedrally coordinated by six O ions, and the O anions are coordinated by two Ta cations and four Na cations. There is presence of structural phase transitions with temperature for NaTaO 3 , and the ideal cubic phase can be observed only at temperatures above 600°C 37–44 . On the other hand, other different crystal structures, as a result of distorting the 3D framework of the linked TaO 6 octahedra, are generally observed at room temperature.…”
Section: Introductionmentioning
confidence: 98%
“…In each TaO 6 octahedron the four O ions lying in planes perpendicular to the b p ‐axis at heights y =0 and y =1/2 are displaced more than the other ions. The TaO 6 octahedra are inclined at an angle of ∼0.4° to b p ‐axis and are rotated about this direction by approximately 2° 38,39 . Because the deviations from the ideal cubic phase are minor, the β angle of the monoclinic structure (Fig.…”
Section: Introductionmentioning
confidence: 99%